The value of organ and tissue biovigilance: a cross-sectional analysis - Navarro, Aurora; Len, Oscar; Muñiz-Diaz, Eduardo; Vives Corrons, Joan-Lluis; Dominguez-Gil, Beatriz; Vilarrodona, Anna; Tort, Jaume (Frontiers in Transplantation, 2024)
Biovigilance (BV) Systems have the purpose of improving the quality and safety of tissues and organs for transplantation. This study describes the Catalan BV system and analyses its utility. It is a retrospective analysis of notifications on serious adverse events (SAEs) and reactions (SARs) since the implementation of the BV System (2008 for tissues and 2016 for organs) until 2020. Variables are presented to describe the most common critical steps of the pathway and complications associated with the quality and safety of tissues and organs. 154 and 125 notifications were reported to the Tissue and the Organ BV systems, respectively. Most SAEs were related to unexpected donor diseases and implemented actions were assured on those deemed preventable. Regarding SARs, donor-transmitted infections and malignancies (only organs) were the most common, followed by graft failure (tissues) and process-related (organs). The incidence of SAEs and SARs related to tissue was 3.44‰ and 0.22‰, respectively. Corresponding figures for organ were 31.48‰ and 8.8‰. The analysis of the notifications to the Catalan BV systems has provided useful information about exiting risks associated with the quality and safety of tissues and organs, and enabled the implementation of actions targeted to diminish risks and mitigate damage.